JOB SATISFACTION AS A KEY FACTOR: CONNECTING WORK ENVIRONMENT AND WORKLOAD WITH THE PERFORMANCE OF EDUCATIONAL STAFF - Rachmatullah, Zaky Noer; Muhardi; Sri Rochani Mulyanti (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the influence of work environment, workload, job satisfaction, and performance of educational staff at Universitas Islam Bandung using a quantitative approach. The sample in this study consisted of 168 educational staff members at Universitas Islam Bandung. The data analysis methods used were descriptive analysis and verification analysis through path analysis. The results of the descriptive analysis indicate that the work environment falls into the category of "fair to good," workload is categorized as "good," job satisfaction is classified as "fair to good," and performance is in the category of "good to very good." The results of the verification analysis show that the work environment has a positive and significant effect on job satisfaction by 45.16%. Workload has a positive and significant effect on job satisfaction by 10.37%. Simultaneously, the work environment and workload have a positive and significant effect on job satisfaction by 74.9%. Job satisfaction has a positive and significant effect on the performance of educational staff by 25.1%. The work environment has a positive and significant effect on the performance of educational staff by 11.49%, while workload has a positive and significant effect on performance by 10.37%. Job satisfaction is able to mediate the influence of the work environment on the performance of educational staff, increasing the effect to 16.99%. Job satisfaction also mediates the influence of workload on performance, increasing the effect to 18.59%. However, job satisfaction is unable to mediate the simultaneous influence of work environment and workload on the performance of educational staff.